Social Capital and Economic Well-Being in Germany's Regions: An Exploratory Spatial Analysis - Botzen, Katrin (REGION, 2016)
This article explores social capital in Germany in line with Putnam’s claim that social capital benefits regional economic well-being. In particular, this macro-level study examines whether the number of civic associations, as a measure of a vibrant civil society, is related to higher GDP. Since this study uses spatial data on civic associations and official statistics concerning the German NUTS-3 regions, different spatial matrices model interdependencies among the dependent units of analysis. Exploratory spatial data analysis illustrates spatial patterns between districts as well as each variable’s radius of influence. Cross-sectional spatial models help examine social capital’s effect on regional economic well-being. Results of these analyses are two-fold: first, the geographical scope of social capital is locally concentrated, whereas the sphere of economic well-being encloses a wider area. Second, social capital correlates positively with economic well-being in Germany’s many regions.